Inclusive CSR and Social Upward Mobility: An Empowerment Framework for People with disabilities in Indonesia’s Rural Industrial Context - Fendy Eko Wahyudi; Muhammad Subhan; Satwika Paramasatya; Ika Nur Halimah; Antika Sukma Pandanarum (International Journal of Research and Community Empowerment, 2026)
Growing attention to inclusive development has emphasized the importance of integrating marginalized groups, including people with disabilities, into economic and social systems, while Corporate Social Responsibility (CSR) initiatives are increasingly expected to move beyond philanthropy toward creating measurable shared value for both companies and communities. This study examines an inclusive CSR and Shared Value Creation (CSV) initiative implemented by PT Pertamina Fuel Terminal Boyolali in collaboration with the Boyolali Disability Communication Forum (FKDB) through the Kresna Patra program, which integrates inclusive education, demand-based vocational training, and job placement for people with disabilities. Employing a qualitative case study design, data were collected through in-depth interviews with 17 key informants, including program beneficiaries, facilitators, CSR representatives, and local government officials, complemented by document analysis of program reports, partnership agreements, and policy frameworks. The study applies the Social Return on Investment (SROI) framework as an integrated evaluation tool to assess the creation of social and economic value. The findings indicate that the program generated an SROI ratio of 2.50, meaning that every Rp 1 invested produced Rp 2.50 in combined social and economic value. In addition, the initiative enhanced participants' self-confidence, employability, and income stability, while strengthening institutional coordination and local policy alignment on disability inclusion. From a CSR perspective, the program demonstrates how inclusive workforce development can generate shared value by aligning corporate operational needs with community empowerment outcomes. The study concludes that CSR initiatives grounded in multi-stakeholder collaboration and evaluative accountability can serve as an effective model for inclusive community development, supporting Sustainable Development Goals 4 (Quality Education) and 10 (Reduced Inequalities), and highlighting the importance of sustained corporate engagement in inclusive economic participation.